Description of a new genus and species of whitefly from Lafoensia pacari in Brazil (Hemiptera, Aleyrodidae, Aleurodicinae) - Martin, Jon H. (Zootaxa, 2011)
Costalimada brasiliensis, gen. and sp. nov. is described from Lafoensia pacari (Lythraceae) in Minas Gerais, Brazil. Its position within the Aleurodicinae is discussed, and an amendment to a previously published key to worldwide genera of Aleurodicinae is presented.